Dampak Perbaikan Infrastruktur Jalan Terhadap Pertumbuhan UMKM di Kecamatan Kota Selatan Kota Gorontalo - Abdul Rahman Usman; Sri Endang Saleh; Sri Indriyani (Masyarakat Ekonomi Syariah Bogor, 2025)
Infrastructure is a semi-primary public facility that plays a role in supporting economic activities in a region. The existence of infrastructure affects the smoothness of people's economic activities and the distribution of goods and services. Infrastructure development in a region aims to improve people's welfare, both economically and socially. This study aims to analyze the effect of road infrastructure improvements on the development of MSMEs in Kota Selatan District, Gorontalo City. The approach used is quantitative by utilizing primary data. The analysis in this study was carried out using a simple linear regression model and processed using IBM SPSS Statistics 25 software. The results of the study show that road infrastructure improvements have a positive and significant effect on MSME growth, with a significance value of 0.000, which is smaller than 0.05. The regression coefficient of 0.726 indicates a positive effect. In addition, the determination coefficient value of 0.489 indicates that road infrastructure improvements contribute to MSME growth by 48.9 percent.